Relative Effectiveness of Inquiry Training Model and Guided Discovery Learning on Critical Thinking of Secondary School Students - V.P, Smitha; Rao, Manjula P. (JOURNAL OF INDIAN EDUCATION, 2011)
Inquiry Training Model and Guided Discovery Learning are two teaching approaches which are known to hold potential in development of critical thinking in students. This study investigated the relative effectiveness of these two approaches. A pre-test post-test quasi-experimental design with a 3 ×2 factorial matrix was adopted. 126 students belonging to three different sections of the eighth standard of a school were selected as the sample. Two classrooms, consisting of 42 students each, were taken as experimental groups in which the Inquiry Training Model and Guided Discovery Learning were applied and the third classroom was the control group which received conventional lecturedemonstration method. The study revealed that both Inquiry Training Model and Guided Discovery Learning were equally effective in developing critical thinking in students and that both these approaches were better than the conventional lecture demonstration method.